(untitled) (The Review of Diabetic Studies, 2025)
Using a content validity method, the current study sought to create and evaluate an Integrated Yoga Module (IYM) especially intended for the treatment of diabetes. The module was methodically created using a multi-phase approach to guarantee its practical viability, therapeutic relevance, and scientific rigor. In Phase I, a thorough literature search of randomized controlled trials published on PubMed between 2014 and 2024 was used to identify yoga practices. Additionally, institutional protocols from the Morarji Desai National Institute of Yoga (MDNIY), traditional yoga literature, especially B.K.S. Iyengar’s Light on Yoga, and professional advice from yoga experts were consulted. The first pool of practices consisted of 21 pertinent studies. The selected practices were divided into five main categories in Phase II: Bandha, Kriya, Asana, Pranayama, and Mudra. The finished IYM has a strong emphasis on yoga techniques that promote pancreas function, boost endocrine balance, improve glucose metabolism, and lessen hyperglycemia brought on by stress. Certain asanas like Surya Namaskar, Mandukasana, Ardha Matsyendrasana, and Sarvangasana are included in the module, along with pranayama methods like Anulom Vilom and Bhramari, cleaning techniques like Kapal Bhati and Agnisar, therapeutic mudras, and Uddiyana Bandha among others. Twenty yoga practitioners with at than five years of experience in yoga therapy or teaching served as an expert panel to validate the content in Phase III. Each method was assessed by experts for safety and applicability in the treatment of diabetes. The IYM’s viability and content validity were validated by the high degree of expert agreement. The validated module offers a solid basis for upcoming clinical trials evaluating its effectiveness on glucose control and metabolic health and can function as a standardized, non-pharmacological supplement for diabetes management.